2003
DOI: 10.1509/jmkr.40.1.65.19129
|View full text |Cite
|
Sign up to set email alerts
|

Stickier Priors: The Effects of Nonanalytic versus Analytic Thinking in New Product Forecasting

Abstract: This research investigates scenario generation and analogical reasoning as potential sources of bias in new product forecasting. In a series of studies, scenarios and analogies were shown to have persistent effects on judgment, despite subsequent use of corrective analytic techniques (counterfactual reasoning, counter-scenarios, counter-analogies, decomposition, accountability). These findings demonstrate the robustness of nonanalytic processes on judgment and the need to be aware of their seductive effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 63 publications
(78 reference statements)
0
40
0
1
Order By: Relevance
“…For example, Sanbonmatsu and Fazio (1990) demonstrated that increasing accountability increases the likelihood that individuals will use attribute information (versus a simpler strategy of relying on overall attitudes) when making memory-based decisions. In a similar vein, Bolton (2003) found that increasing accountability leads individuals to work harder and create more elaborate scenarios when forecasting future events.…”
Section: Overview Of the Hypothesesmentioning
confidence: 93%
“…For example, Sanbonmatsu and Fazio (1990) demonstrated that increasing accountability increases the likelihood that individuals will use attribute information (versus a simpler strategy of relying on overall attitudes) when making memory-based decisions. In a similar vein, Bolton (2003) found that increasing accountability leads individuals to work harder and create more elaborate scenarios when forecasting future events.…”
Section: Overview Of the Hypothesesmentioning
confidence: 93%
“…Nevertheless, considering counter-explanations that are implausible or diYcult to generate strengthens the bias towards prior beliefs (Hirt and Markman 1995;Dougherty et al 1997;Kadous et al 2006). Scenario anchoring eVects appear to be less prominent in multiple explanation research than in the forecasting studies reviewed above (Schnaars and Topol 1987;Kuhn and Sniezek 1996;Bolton 2003). This is perhaps because in multiple explanation studies participants do not themselves explicitly generate the kind of detailed narrative scenarios that require signiWcant cognitive eVort and encourage the development of elaborate schemas that act as anchors on judgments, which are evidently not so easy to shift.…”
Section: Scenariosmentioning
confidence: 99%
“…For instance, in a study of new product forecasting Bolton (2003) found that participants who Wrst generated a scenario depicting a successful outcome then generated an opposing failure scenario were signiWcantly more optimistic about the product's future than those who generated scenarios in the opposite order. Moreover, when the researchers attempted to debias participants' judgments by presenting information conXicting the scenarios generated, participants actually shifted their judgments further in the direction of the Wrst scenario considered; that is, debiasing eVorts exacerbated the primacy bias.…”
Section: Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that most theoretical insights in management cognition stem from controlled environments (Oliver and Roos, 2005) is valid also with respect to analogising, although the agent-simulation approach of complements earlier experimental studies (Isenberg, 1988;Dahl and Moreau, 2002;Bolton, 2003). examine competitive positioning based on analogising across industries.…”
Section: Introductionmentioning
confidence: 99%